EMISI GAS RUMAH KACA DI PERKEBUNAN KARET - Priyo Adi Nugroho (Warta Perkaretan, 2016)
Carbon dioxide (CO2) and nitrous oxide (N2O) and methane (CH4) are three of the major greenhouse gas (GHG). Agricultural sector accounts for 10-14% of global athropogenic GHGs. The research of GHGs in rubber plantation has been started in several rubber producer countries including Indonesia however the progress is not as fast as in other agricultural commodities. Carbon stock and carbon balance in rubber plantation is the trending research topic. Biometric and eddy coveriance are the two methods that are used for investigating carbon emission. The results of some study using those two methods indicate that the similar result i.e. the amount carbon that is released by rubber plantation ecosystem is tended to be smaller than carbon absorption. The amount of CO2 that absorbed by rubber plantation is approximately 29-40 tons CO2 ha/year. Commonly the previous studies are mostly conducted in establish area, which mean the study is not designed with some treatments such as fertilizer and organic matter dosage, time of application, soil tillage. The deeply study of carbon emission, related to field management to carry out the best management practices and environmental friendly is still needed. The similar study concerning other gas like N2O in rubber plantation is also important to be conducted. It is due to the application of nitrogen fertilizer and organic matter in rubber plantation is high enough. There are some opportunities to conduct research consortium with other research institutions and universities in order to solve the high cost in GHGs research.